(untitled) (Medico Legal Update, 2019)
The research is to carry out new strategies for the application of advanced information system on the strengthening pelvic muscle for treatment of uterine prolapse. The data consisted of 142 women who visited the gynecology of a university hospital. After the survey, it was carried out by a one-on-one interview from February 5 through April 13, 2018. The pelvic reinforcement was measured by t-test. The continuation of immunity and muscle strength were compared to 7, 14, 21, 28, 35, and 42 days and prior to the application of the latest system. The results obtained are as follows. 1) The data has been shown that 52.4% of people who exercise regularly is significantly less than 46.0% of the comparative people(X2=3.91, p<.05). 2) 47.9% of people who drank frequently were significantly higher than 28.2% of the comparative people(X²= 4.26, p<.05). 3) The pelvic examination was significantly higher after the application than before the application of the latest system. 4) The kegel exercise had increased significantly since the application of the system than before the application of it(t=-3.84, p<.01). 5) Bending and stretching both legs were significantly higher after applying the system than before applying it(t=-1.65, p<.01). 6) Seven days later, the immunity of pelvic organ was improved rapidly in the investigation people than comparative people. 7) It has been shown that strengthening pelvic muscle has increased in the case population after application of it than before the information system was applied. But it has decreased somewhat since the 21 days in the test people than comparative people. The data has been shown to be effective in treating pelvic organ prolapse. lt is expected to contribute to the effect if the system applied to other organ prolapse.